JUAL BELI DENGAN SISTEM ARISAN KABUPATEN KOTA WARINGIN TIMUR DESA SAMUDA - Muhammad Amin (Institut Agama Islam Negeri Metro, 2023)
Along with its development, buying and selling have been carried out through the gathering system. Buying and selling with the gathering system aims to help meet the needs of the gathering participants and help sell merchant merchandise. Apart from the benefits, there are also several problems when buying and selling with this system, as happened in a village in Indonesia where gold is a commodity object. This type of research is empirical juridical research with a socio-legal approach. Data collection techniques in this study were observation, interviews, and documentation. This study aims to determine the practice of buying and selling using the gathering system in Samuda Village, East Kotawaringin Regency, Central Kalimantan. The result shows that buying and selling with the gathering system is istishna and permissible to implement. However, if there are gathering participants who default, it will provide a gap for losses to one of the parties. Then, the objects of buying and selling by the gathering system carried out by the people in the village are various kinds of goods. However, when the practice of buying and selling through the gathering system with gold jewelry objects, the law is prohibited based on the losses experienced by the gathering participants and the prohibition in Islam against crediting gold, it can be concluded that the law of gold gathering is unlawful. Hopefully, this research can provide understanding to the public to avoid harmful buying and selling and can increase Sharia buying and selling.